Evaluating the effectiveness of mobile app-based self-guided psychological intervention to reduce craving and lapse risk in problematic substance use and behaviors: Protocol for a randomized control trial in the general population - Alicja Anna Binkowska; Katarzyna Obarska; Przemysław Marcowski; Karol Szymczak; Karol Lewczuk; Katarzyna Sollich; Maria Banaszak; Bohdan Woronowicz; Małgorzata Nowicka; Maciej Skorko; Mateusz Gola (Contemporary Clinical Trials Communications, 2023)
Background: The prevalence of substance and behavioral addiction is estimated between 10 and 15% of the global population and remains a severe public health concern. Moreover, addiction treatment has several barriers, such as a lack of access to professional treatment or stigmatization. Mobile health interventions emerge as a promising solution. Methods: This two-armed randomized controlled trial (RCT) aims to assess the efficacy of a mobile app-based self-guided psychological intervention delivered via a smartphone app (Nałogometr) in reducing craving and lapse risk in problematic behaviors and substance use compared to a control condition. Participant recruitment and data collection will start in June 2022 and end in September 2022. Due to the nature of the study, i.e., a nationwide study of problematic substance use and behaviors, we will aim to recruit all individuals willing to participate. The four-week intervention condition includes short-term and long-term modules based mainly on mindfulness and cognitive behavioral therapy. Longitudinal data on several variables related to craving and lapse risk are collected daily using ecological momentary assessment (EMA). The primary outcomes of interest will be the self-reported number of lapses and craving level in daily EMA. Moreover, a questionnaire battery assessment is administered at baseline in the first week following onboarding, after five weeks, and after six months. The secondary outcome measures will include the severity of problematic substance use or behaviors, anxiety and depression, and life satisfaction. Results: Results will be submitted for publication in peer-reviewed journals. Clinical trial registration: [https://clinicaltrials.gov/], identifier [NCT054 34,429].